Exploring physiotherapy practice within hospital-based interprofessional chronic pain clinics in Ontario. Issue 1 (1st January 2021) - Thacker, Linnea; Walsh, Robert M.; Shinyoung Song, Gabriella; Khan, Hammad A.; Parmar, Prem; Vance, Kaitlin T.; Grant, Gillian; Mesaroli, Giulia; Hunter, Judith; Vader, Kyle
ABSTRACT: Background : Chronic pain affects one in five persons and is a leading contributor to years lived with disability and high health care costs. In 2016, the government of Ontario increased public funding for pediatric and adult hospital-based interprofessional chronic pain clinics (HICPCs) in Ontario, Canada, expanding the role of physiotherapy in chronic pain management in the province. This role has yet to be described in the literature. Aim : The aim of this study was to explore physiotherapy practice within HICPCs in Ontario. Methods : We conducted an interpretive description qualitative study based on semistructured interviews with physiotherapists employed in pediatric and adult HICPCs in Ontario. Interviews were audio recorded, transcribed verbatim, and reviewed for accuracy. We analyzed interview data using thematic analysis. Results : Ten physiotherapists who practiced in pediatric and adult HICPCs ( n = 4 pediatric; n = 6 adult) in Ontario were interviewed between February and April 2020. We constructed five themes related to physiotherapy practice in this setting. Themes included (1) contributing a functional lens to care; (2) empowering through pain education; (3) facilitating participation in physical activity and exercise; (4) supporting engagement in self-management strategies; and (5) implementing a collaborative approach to whole-person care. Conclusions : Our results illuminate how physiotherapy practice within HICPCs in Ontario focuses on providing a collaborative and whole-person approach to care, with an emphasis on supporting patients to increase their functional capacity by promoting engagement in active chronic pain management strategies.